We're all a little mental here : creating positive change through mental health advocacy in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology, Massey University, Manawatū, New Zealand - Brown, Samuel Gareth (Massey University, 2015)
The following paper explores mental health in New Zealand, and argues for further positive change to occur in this area. This argument is derived from the interviews I undertook with mental health advocates, who seek positive change for consumers through their day-to-day work. My own experiences as a mental health consumer also inform this paper, and position me as both a researcher and advocate. Data analysis takes the form of hermeneutic phenomenology, as this method privileges the advocates narratives, which are typically minimised by mental health specialists. Theoretically, these narratives are analysed through the lens of Foucauldian social constructionism, in order to show how the current dominant biomedical discourse has come into being, and also how this discourse can be challenged, as it represents one of the largest barriers to positive change for mental health in New Zealand.
Keywords: Mental health services, New Zealand